2006
DOI: 10.1002/app.24143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 25 tropical hardwoods with Fourier transform infrared, ultraviolet resonance Raman, and 13C‐NMR cross‐polarization/magic‐angle spinning spectroscopy

Abstract: Twenty-five tropical hardwoods from Ghana were examined with Fourier transform infrared (FTIR), ultraviolet resonance Raman (UVRR), and 13 C-NMR crosspolarization/magic-angle spinning spectroscopy. FTIR and UVRR spectral data were subjected to principal component analysis, whereas four selected samples exhibiting large structural and compositional variation were investigated in more detail by NMR spectroscopy. The acetyl bromide lignin and ␣-cellulose contents of the samples and the amount of acetone-soluble s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
0
43
2
1
Order By: Relevance
“…Only, H. plagata contained significantly less lignin (-16%) than the other species (Table 1). All lignin concentrations reported here are at the lower end of those reported in other investigations for tropical tree species (Fengel et al 1983;Saka 2001;Pastore et al 2004;Nuopponen et al 2006;Jahan and Mun 2007;Santana and Okino 2007). The low lignin concentration of H. plagata was surprising since this species is reported to be among the most durable dipterocarps (Newman et al 1996) pointing to other factors as determinants of durability.…”
Section: Lignin Carbon and Nitrogen Concentrationscontrasting
confidence: 49%
See 1 more Smart Citation
“…Only, H. plagata contained significantly less lignin (-16%) than the other species (Table 1). All lignin concentrations reported here are at the lower end of those reported in other investigations for tropical tree species (Fengel et al 1983;Saka 2001;Pastore et al 2004;Nuopponen et al 2006;Jahan and Mun 2007;Santana and Okino 2007). The low lignin concentration of H. plagata was surprising since this species is reported to be among the most durable dipterocarps (Newman et al 1996) pointing to other factors as determinants of durability.…”
Section: Lignin Carbon and Nitrogen Concentrationscontrasting
confidence: 49%
“…The low lignin concentration of H. plagata was surprising since this species is reported to be among the most durable dipterocarps (Newman et al 1996) pointing to other factors as determinants of durability. Durability in tropical hardwoods is affected by the combination of wood density and the content and composition of lignin and extractives (Onuorach 2000;Nuopponen et al 2006). It must, therefore, be considered that the five species of our study differ in their contents of extractives and wood densities.…”
Section: Lignin Carbon and Nitrogen Concentrationsmentioning
confidence: 91%
“…Additionally, it was reported that, although present in significant quantity (20-30%), very few hemicellulose Raman contributions were detected. In more recent work [19], ultraviolet resonance Raman (UVRR) in conjunction with principal component analysis has been used to characterize woods, and using this approach, it was possible to distinguish between various aromatic and other unsaturated structures in wood.…”
Section: Woodsmentioning
confidence: 99%
“…We expect that UVRR spectroscopy will be able to provide information on not only the presence of a Trp residue, but also on the structure and environment of Trp in the native state in the cocoon, because the UVRR spectrum is sensitive to the structure and environment in relation to the side chains of aromatic compounds in the solid state. 7) Moreover, the UVRR spectrum reflects the conformational properties of Trp in proteins.…”
Section: )mentioning
confidence: 99%
“…6) Moreover, recent developments in UVRR have enabled the detection of solid materials. 7) However, this technique has never been applied to the structural analysis of fibrous proteins in the solid state, to our knowledge.…”
mentioning
confidence: 99%